The impact of family factors and communication on recreational sedentary screen time among primary school-aged children: a cross-sectional study - Xueting Ding; Ying Ji; Yuan Dong; Zhijing Li; Yan Zhang (BMC, 2024)
Abstract Background Childhood obesity is increasingly recognized as a major public health challenge worldwide, and excessive sedentary screen time is emerging as a key risk factor. This study aimed to assess the recreational screen sedentary time of Chinese primary school-aged children and investigate the relationship between screen-related family factors and the outcome variable. Methods Our study used data from a cross-sectional survey collected from fifth-grade students and their parents in Beijing, China, from April to May 2018 (n = 2,373). The questions included basic demographic information, family socioeconomic status, students' and parents' sedentary and exercising habits, within-family communicational factors, and health belief patterns. The recreational screen sedentary time of the children was compared across demographic groups. The study employed multivariate linear regression models to examine associations between children's screen time and various family factors, as well as the moderating effect of overall family communication. Results Our findings revealed an average daily recreational screen sedentary time of 2.4 h among participants. Screen time significantly varied across demographic categories, including children's sex, age, residence, parents' education, household income, family size, and primary family member. After adjustment, the proportion of child-owned digital devices (p < 0.01), child's personal room (p < 0.05), family screen-viewing together (p < 0.01), and parental screen time (p < 0.01) were positively related to children's recreational sedentary screen time. Parental restrictions on screen time (p < 0.001) and attitudes toward reducing sitting time (p < 0.01) were correlated with a decrease in children's screen time. The overall family communication environment significantly moderated the effects of parental practice of restricting children's screen time (p < 0.001), positive reinforcement by parents (p < 0.05), and parents' recreational sedentary screen time (p < 0.001). Conclusions Our findings underscored the significance of family dynamics, parental practices, and communication in shaping children's screen time behaviors, providing valuable insights for tailored interventions and strategies to reduce childhood obesity.